Distinct Transcriptional Profiles in the Different Phenotypes of Neurofibroma from the Same Subject with Neurofibromatosis 1 - Wang, Wei-Ning; Koguchi-Yoshioka, Hanako; Nimura, Keisuke; Watanabe, Rei; Tanemura, Atsushi; Fujimoto, Manabu; Wataya-Kaneda, Mari (Journal of investigative dermatology, 2024)
Neurofibromatosis 1 is a prevalent hereditary neurocutaneous disorder. Among the clinical phenotypes of neurofibromatosis 1, cutaneous neurofibroma (cNF) and plexiform neurofibroma (pNF) have distinct clinical manifestations, and pNF should be closely monitored owing to its malignant potential. However, the detailed distinct features of neurofibromatosis 1 phenotypes remain unknown. To determine whether the transcriptional features and microenvironment of cNF and pNF differ, single-cell RNA sequencing was performed on isolated cNF and pNF cells from the same patient. Six cNF and five pNF specimens from different subjects were also immunohistochemically analyzed. Our findings revealed that cNF and pNF had distinct transcriptional profiles even within the same subject. pNF is enriched in Schwann cells with characteristics similar to those of their malignant counterpart, fibroblasts, with a cancer-associated fibroblast–like phenotype, angiogenic endothelial cells, and M2-like macrophages, whereas cNF is enriched in CD8 T cells with tissue residency markers. The results of immunohistochemical analyses performed on different subjects agreed with those of single-cell RNA sequencing. This study found that cNF and pNF, the different neurofibromatosis phenotypes in neurofibromatosis 1, from the same subject are transcriptionally distinct in terms of the cell types involved, including T cells.